Development of a novel clinical support tool for active surveillance of low risk papillary thyroid cancer - White, Eleanor; Abbott, Bridget; Schembri, Geoffrey; Glover, Anthony; Clifton-Bligh, Roderick; Gild, Matti L. (Frontiers in Endocrinology, 2023)
Background: Active surveillance (AS) is an alternative to surgery in select patients with very low risk papillary thyroid cancer (PTC). Many clinicians feel ill-equipped in selecting appropriate patients. We aimed to 1) Develop an evidence-based web delivered decision support tool to assist clinicians in identifying patients appropriate for AS; and 2) Evaluate the prevalence of patients suitable for AS in a tertiary high volume thyroid cancer centre. Method: A REDCap web based clinical support tool was developed utilising evidence-based characteristics for AS suitability available to clinicals during initial assessment. A retrospective database was interrogated for patients who underwent hemithyroidectomy between 2012 – 2021 with final histopathology demonstrating PTC. Patients with PTCs>2cm, missing data, benign disease on surgical histopathology or incidental PTC were excluded. Results: Between 2012 - 2021, 763 patients underwent hemithyroidectomy with final histopathology confirming PTC. Of these, 316 patients were excluded (missing data, incidental PTC, concomitant hyperparathyroidism were most common reasons for exclusion) and 114/447 remaining patients had a pre-operative fine needle aspirate (FNA) of Bethesda V or VI (high likelihood of malignancy). Using the tool, 59/114 (52%) met criteria for AS. The majority of patients were female (85% vs 15% male); median age 36 years (range 19 – 78). Following initial surgery, 10/59 patients had a completion thyroidectomy, with 4/10 demonstrating malignancy in contralateral lobe and eight of those patients undergoing I131 ablation. During a median follow up of over 3 years, 49/59 (83%) did not require further surgery or intervention with no patients developing recurrence. A subgroup analysis with second radiology assessment excluded 4/59 patients as meeting criteria for AS based on presence of ETE on preoperative ultrasound. None of these 4 patients had completion thyroidectomy. Conclusion: Our clinical support tool identifies patients with PTC potentially suitable for AS which could be utilised during initial patient assessment. In a retrospective cohort of patients who had hemithyroidectomy for PTC with a pre-operative FNA diagnosis of Bethesda V or VI, 55/114 (48%) patients may have been suitable for AS. Prospective validation studies are required for implementation of the tool in clinical practice.